Effect of gradation on macro-meso shear properties of the alluvial-diluvial soil-rock mixture (ADSRM) - Liu, Longqi; Fan, Zhenhao; Yao, Linhu; Yang, Yunshu (Frontiers in Materials, 2024)
Alluvial-diluvial soil-rock mixture (ADSRM) is a unique geological material primarily consisting of pebbles, gravel, and soil. Gradation design significantly enhances the shear strength of ADSRM, offering significant implications for sustainable construction of transportation infrastructure in mountainous regions. Hence, the N-method of gradation theory was employed for the gradation design of ADSRM fillers in this study. Macromechanical testing reveals that the graded sample exhibits significantly higher shear strength, equivalent cohesion, and friction angle compared to the ungraded sample, with more pronounced shear dilatancy. Meso-shear properties suggest that the graded sample has a lower percentage of pore area compared to the ungraded sample, but a higher percentage of small pores relative to total pores, and more crushed rock blocks under the same normal stress conditions. Pore abundance indicates that the majority of pores on the shear plane are oblate in shape. The findings from the equivalent diameter and fractal dimension of the rock block contour suggest improved grinding roundness of rock blocks in the graded sample postshearing. In summary, the quantity of pores and broken rock blocks primarily impacts the strength and equivalent cohesion of the filler, while the abundance, roundness, shape coefficient, and fractal dimension of rock block contour mainly affects the internal friction angle.